Islamic Marketing Management for SMEs - Arif, Widyantono; Siradjuddin, Siradjuddin (Interdisciplinary Social Studies, 2021)
Background: Small and Medium Enterprises (SMEs) are the most popular group of companies in the national economy (Kanibir, Saydan and Nart, 2014). The company must be effective in every activity especially in marketing which has become fundamental to success in the market and create a competitive advantage. Aim: The purpose of this article is to reveal the stages of the task of a marketing manager/small and micro sharia businessman in carrying out marketing activities that can help achieve organizational goals. Method: The researchers deployed qualitative approach by reviewing relevant articles. Findings: The Elements of the Marketing Mix are products, prices, places, promotion, people, physical evidence, and process. Thus the task of marketing managers / small business entrepreneurs and micro-sharia is to choose and carry out marketing activities that can help achieve organizational goals.